Evaluation of the drug-drug interaction potential of the novel hepatitis B and D virus entry inhibitor bulevirtide at OATP1B in healthy volunteers - Zhu, Vanessa; Burhenne, Jürgen; Weiss, Johanna; Haag, Mathias; Hofmann, Ute; Schwab, Matthias; Urban, Stephan; Mikus, Gerd; Czock, David; Haefeli, Walter E.; Blank, Antje (Frontiers in Pharmacology, 2023)
Introduction: Bulevirtide is a first-in-class antiviral drug to treat chronic hepatitis B/D. We investigated the drug-drug interaction potential and pharmacokinetics of high-dose subcutaneous bulevirtide (5 mg twice daily) with organic anion transporting polypeptide 1B1 (OATP1B1) and cytochrome P450 (CYP) 3A4. Methods: This was a single-center, open-label, fixed-sequence drug–drug interaction trial in 19 healthy volunteers. Before and at bulevirtide steady state, participants ingested a single 40 mg dose of pravastatin. A midazolam microdose was applied to quantify CYP3A4 activity. Results: At bulevirtide steady state, pravastatin area under the concentration-time curve (AUC0–∞) increased 1.32-fold (90 % CI 1.08-1.61). The 5 mg bulevirtide twice-daily treatment resulted in a mean AUC0-12 of 1210 h*ng/mL (95% CI 1040-1408) and remained essentially unchanged under the influence of pravastatin. CYP3A4 activity did not change to a clinically relevant extent. As expected, total bile acids increased substantially (35-fold) compared to baseline during bulevirtide treatment. All study medication was well tolerated. Discussion: The study demonstrated that high-dose bulevirtide inhibited OATP1B-mediated hepatic uptake of the marker substrate pravastatin but the extent is considered clinically not relevant. Changes in CYP3A4 activity were also not clinically relevant. In conclusion, this study suggests that OATP1B substrate drugs as well as CYP3A4 substrates may safely be used without dose adjustment in patients treated with bulevirtide. However, in patients using high statin doses and where concomitant factors potentially further increase statin exposure, caution may be required when using bulevirtide.